(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
In this study, it was planned to obtain oil by cold pressing by mixing black sedan and sunflower seeds in ratios of 50:50; 70:30; 80:20. Procedures for the oil refining from this mixture by physical methods while preserving the bioactive components were studied. Black sedana seed has a pronounced bitter taste, which is an obstacle to daily use in the food industry, but heals the body and various shells due to a high richness of biologically active substances. With this in mind, it was planned to combine black sedana oil with sunflower seeds, soften the taste and smell, and obtain a functional ointment containing the active compounds of the two seeds. The reason why sunflower seeds are chosen as a side seed is because this seed oil has already become widespread as an everyday oil, it is economical to be cheap, the smell and taste are much smoother, which does a lot to promote the normalization of the taste and smell of black sedan oil, and is very rich in unsaturated fatty acids. The oil obtained by pressing both seeds together, on the one hand, increases the stability of sunflower oil at the expense of antioxidants of black sedan, while sunflower oil with tocopherol and useful fatty acids greatly contributes to increasing biological activity, as well as improving orgonoleptic parameters. Our study allowed us to physically purify oils of three different ratios and observe how the ratio of seeds affects the oil.